EBV and Concomitant Acute Motor and Sensory Axonal Neuropathy in a Healthy 15-Year-Old Female - Basch, Rebecca E.; Tierney, McKenna; Worden, Lila; Sanders, Sara; Ng, Elizabeth A. (Neuropediatrics, 2025)
Acute motor and sensory axonal neuropathy (AMSAN) is a rare and severe form of acute axonal injury caused by immune damage to the axonal membrane. AMSAN is an axonal variant of GBS. GBS occurs from immune injury to the myelin sheath, axonal variants of GBS (AMSAN and AMAN) differ in that insult is to the axonal membrane. AMSAN is seldom seen, especially in pediatric and adolescent patients. Unlike acute motor axonal neuropathy (AMAN), which has been well-described in literature to be secondary to Campylobacter jejuni infection, there is no known etiology of AMSAN. Here, we present a case of an otherwise healthy 15-year-old female who presented with new-onset facial and bulbar weakness that rapidly progressed to functional paralysis requiring intubation. With no clear diagnosis and after failure in improvement with high-dose steroids, Intravenous Immunoglobulin (IVIG), and plasma exchange transfusion, diagnosis was finally made with electromyography (EMG) and nerve conduction study (NCS). In addition, extensive laboratory work was completed and was only notable for primary acute EBV infection. This case represents a new presenting symptom of AMSAN, a unique finding of concomitant primary EBV infection, the possibility of primary Epstein–Barr virus (EBV) infection as the triggering event in AMSAN and stresses the importance of EMG and NCS when evaluating patients with weakness.
Keywords: acute motor and sensory axonal neuropathy; acute inflammatory demyelinating polyneuropathy; Epstein–Barr virus; acute motor axonal neuropathy